An investigation of premature fatigue cracks of F-5 fuel tank fin. (August 2015) - Lee, Bok-Won; Choi, Dong-Su
Highlights: Fins of center fuel tank of F-5 aircraft experienced premature fatigue cracks. Fatigue cracks were induced from buffet generated by the extension of speed brake. Composite patch repair was successfully employed to retard crack growth. Abstract: Horizontal fins of the F-5 external center fuel tanks (150 gallon) experienced severe cracks through the entire fleet of Republic of Korea Air Force (ROKAF) hereafter. Special inspection showed that most horizontal fins of center fuel tanks have similar cracks at identical locations. Most cracks have developed and exceeded the repairable limitation. Less than 100 flights have led to their premature fatigue failure, costing huge budget every year for replacement. This paper describes the failure investigation, which established that the horizontal fins failed due to fatigue cracking, and includes fractography and finite element analysis to describe failure mechanism. The results strongly suggest that the cracking was induced from the vortex flow generated by the extension of speed brake. All findings were utilized to develop structural repair method by employing reinforcement of the graphite/epoxy composite patch which was responsible for crack growth retardation.